The Relevance of Ibn Khaldun’s Economic Thought on The Prices Mechanism in The Modern Economy - Nisak, Khoirun (Invest Journal of Sharia & Economic Law, 2022)
Ibn Khaldun is known as one of the Muslim scholars who made significant contributions to the social sciences, including economics. Ibn Khaldun developed his thoughts on the price mechanism in the market by looking at the condition of Andalusian society at that time. This study aims to discover Ibn Khaldun's thoughts regarding the price mechanism, both from the supply and demand sides, and whether these thoughts remain relevant to today's economic phenomena. The results of the analysis show that naturally,  the price in the market is formed due to the process of attraction between demand and supply. This research found that people's tastes are a factor that shifts the demand curve.   Meanwhile, product scarcity and production costs shift the supply curve. Ibn Khaldun's thought aligns with modern economic theory and remains relevant to present economic phenomena.